Surge in Mycoplasma Pneumoniae infection and Respiratory Viruses Co-infection in Children With Community-Acquired Pneumonia in the Post-Pandemic - Chi J; Tang H; Wang F; Wang Y; Chen Z (Dove Medical Press, 2024)
Jie Chi, Heng Tang, Fang Wang, Yuxuan Wang, Zhifeng Chen Department of Pharmacy, Tongling Municipal Hospital, Tongling, Anhui, People's Republic of ChinaCorrespondence: Zhifeng Chen, Department of Pharmacy, Tongling Municipal Hospital, Tongling, Anhui, People's Republic of China, Tel +8613856231378, Email 47986687@qq.comPurpose: During the COVID-19 pandemic, multifaceted non-pharmaceutical interventions have not only reduced the transmission of SARS-CoV2 but also affected the prevalence of other respiratory pathogens. With the lifting of many restrictions, a surge in cases of pneumonia in children has been reported in many hospitals in China. The study assessed the changes in pathogen and symptoms of children with community-acquired pneumonia (CAP) before and after the adjustments of prevention and control measures of epidemic and provided recommendations for CAP in children.Patients and methods: Children diagnosed with CAP were enrolled in the study from 2022 to 2023. A cross-sectional retrospective study was conducted in a general hospital. We analyzed the data about demographic data, clinical symptoms, pathogens, and medical treatments. The Chi-square and Mann-Whitney U-test were used to assess the statistical significance of groups.Results: We studied 1103 children, 339 in 2022 and 764 in 2023. Compared with children in 2022, more children were diagnosed with CAP in 2023 and these children had a higher body temperature and levels of CRP and PCT, which indicated these children got severe inflammation. The positive rate of the pathogen was also higher in 2023, especially the detective rate of Mycoplasma pneumoniae. The number of children infected with more than two pathogens was higher in 2023, especially those co-infected with the virus and M. Pneumoniae. Concerning the medicine therapy, the usage of β-lactam antibiotics, Macrolide antibiotics, and antiviral drugs kept rapid growth.Conclusion: After the adjustment of epidemic prevention and control policies in 2023, more children got CAP with severe clinical symptoms, and more antibiotics and antiviral drugs were used. Further study is needed to explore the reasons for the increase in children with CAP and to explore the rationality of treatment.Keywords: community-acquired pneumonia, children, post-pandemic, pathogen